SIGNIFICANCE OF GLYCAEMIC CONTROL IN TYPE 1 DIABETES - Wahid, Maryam; Naveed, Abdul Khaliq (Journal of Ayub Medical College Abbottabad, 2013)
Background: Diabetes mellitus is accompanied with drastic hormonal and metabolic alterations. In uncontrolled diabetes, these disturbances worsen the condition leading to development of life threatening complications. Present study was planned to compare hormonal and metabolic disturbances in controlled and uncontrolled type 1 diabetes (T1D). Methods: This retrospective, analytical case control study was carried out from Jan 2004 to July 2007. Sample size was 60, divided into 3 groups: Non-diabetic control (group A), controlled T1D (group B) and uncontrolled T1D (group C). Results: Uncontrolled type 1 diabetics when compared with control group, presented with significant hyperglycaemia (p<0.001), hypoinsulinemia (p<0.001), hyperglucagonemia (p<0.01), raised BMI (p<0.05), hyponatremia (p<0.01), hyperkalemia (p<0.01), acidemia (p<0.05), high arterial Pco2 (p<0.05), low plasma HCO3- (p<0.05), raised plasma triglyceride, LDL Cholesterol and total cholesterol level (p<0.01) but low HDL cholesterol (p<0.05). On similar comparison controlled type 1 diabetics showed significant hyperglycaemia (p<0.001) and hypoinsulinemia (p<0.05). Conclusion: Regular assessment, monitoring and control of T1D has positive impact in preventing development of diabetic dyslipidemia and other hormonal and metabolic derangements which, if left uncontrolled can lead to life threatening diabetic complications. Keywords: Type 1 diabetes, Diabetic Ketoacidosis, Dyslipidemia, Hypoinsulinemia, Hyperglycaemia, hyperglucagonemia